2018
DOI: 10.3389/fphys.2018.01189
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Inhibitor, IMD-0354, Affects Immune Gene Expression, Bacterial Microbiota and Trypanosoma cruzi Infection in Rhodnius prolixus Midgut

Abstract: Rhodnius prolixus is an insect vector of Trypanosoma cruzi, the causative agent of Chagas disease in Latin America. Nuclear factor-κB (NF-κB) transcription factors (TF) are conserved components of the innate immune system in several multicellular organisms including insects. The drug IMD-0354 [N-(3,5-bis-trifluoromethyl-phenyl)-5-chloro-2-hydroxy-benzamide] is a selective inhibitor of IκB kinases. It blocks IκBα phosphorylation thus preventing nuclear translocation of the NF-κb TF. In humans, NF-κB is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 67 publications
3
31
1
Order By: Relevance
“…The AMPs involved in these studies are likely controlled by the Toll and IMD pathways as silencing the NF-κB transcription factor relish (IMD pathway) reduces the intestinal bacterial population while the opposite occurs when the NF-κB transcription factor dorsal (Toll pathway) is silenced [251]. The pharmacological inhibition of these pathways also affects AMP expression and reduces the microbiota levels [250]. Despite the effects on the microbiota, T. cruzi numbers remain unaltered when either pathway is silenced, suggesting that T. cruzi can tolerate the immune responses or actively induces some of these changes to regulate the microbiota [251,267].…”
Section: Effects Of Trypanosomes On the Microbiotamentioning
confidence: 99%
“…The AMPs involved in these studies are likely controlled by the Toll and IMD pathways as silencing the NF-κB transcription factor relish (IMD pathway) reduces the intestinal bacterial population while the opposite occurs when the NF-κB transcription factor dorsal (Toll pathway) is silenced [251]. The pharmacological inhibition of these pathways also affects AMP expression and reduces the microbiota levels [250]. Despite the effects on the microbiota, T. cruzi numbers remain unaltered when either pathway is silenced, suggesting that T. cruzi can tolerate the immune responses or actively induces some of these changes to regulate the microbiota [251,267].…”
Section: Effects Of Trypanosomes On the Microbiotamentioning
confidence: 99%
“…Therefore, we screened multiple related compounds and found that N-(3,5-bis-trifluoromethyl-phenyl)-5-chloro-2-hydroxybenzamide (IMD 0354) is a non-ATP binding competitive and selective molecular inhibitor of IKK-β. IMD 0354 has been reported in several studies as an effective agent for the treatment of acute and subacute inflammatory diseases including myocarditis, pulmonary arterial hypertension, and diabetic retinopathy via the suppression of NF-κB activation in various cells, such as pulmonary arterial smooth muscle cells or myocardial cells [18][19][20][21] . There are considerable issues in regard to the drugs for osteoporosis treatment currently.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the expression of Relish and Cactus regulates infection prevalence and intensity, highlighting the importance of the IMD and Toll pathways in anti-parasitic immune responses in vectors ( Meister et al., 2005 ; Frolet et al., 2006 ; Hu and Aksoy, 2006 ; Antonova et al., 2009 ; Louradour et al., 2019 ). In this regard, a recent report demonstrated a reduction in T. cruzi loads in the midgut of R. prolixus treated with the drug IMD-0354, which impedes the activation of NF-κB TFs ( Vieira C. S. et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primers were designed for: α-Actin (housekeeping), Rp-Relish , Rp-Dorsal , Rp-Caspar , and Rp-STAT . Primers for Rp-Cactus were retrieved from the literature ( Vieira C. S. et al., 2018 ). RT-qPCR efficiency for each primer pair was determined using the slope of a linear regression mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation